İstanbul Filarmoni Derneği'nin çoksesli müziğimize katkıları - Bilget, Halil Mehmet (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü, 2009)
Çalışmamızın konusu İstanbul Filarmoni Derneği'nin kuruluşundan bugüne kadar olan sürecin bütün olarak ele alınmasıdır. Bu süreç içerisinde İstanbul Filarmoni Derneği'nin ülkemizin çok sesli müzik hayatındaki yeri ve önemi de çalışmamız içerisinde yer alır. Derneğin kuruluşu, çalışmaları, gelişimi de çalışma konumuzdur. Çalışmamız sırasında en önemli kaynağımız İstanbul Filarmoni Derneği'nde çalışma fırsatı bulmuş kişiler olmuştur. Yaptığımız röportajlar ışığında bilgiler toplanmış, derneğin arşivi ve dönemin sanat etkinliklerini konu edinmiş müzik dergileri taranmıştır. Ulaşabildiğimiz kaynaklar ve bilgiler toplanarak tez çalışmamız oluşturulmuştur. Çalışma, kuruluşundan itibaren yetiştirdiği amatör öğrenciler, gençler ve profesyonel sanatçılarla Türkiye çoksesli müziğinde her zaman söz sahibi olan İstanbul Filarmoni Derneği'nin öyküsüdür.

Our study is focus is to analyze the period as a whole, starting from the establishment of Istanbul Philarmonic Society until today. During this period, the importance and the role of Istanbul Philarmonic Society in our country?s poliphonic music life and history also takes place in our work. Establishment, development and the studies of the society is also amongst the topics of our work. During our research, our most important resource was the individuals who had the opportunity of working in Istanbul Philarmonic Society. We gathered the information in the light of the interviews made, Society?s archives and through scanning the music journals of the period giving place to the musical activities of the time. Our thesis is derived from the resources and the information that was accesible to us. This study is the story of Istanbul Philarmonic Society, which always has a say in Turkish poliphonic music through the amateurs and professional musicians it brought up from the day it was established.
Istanbul Philarmonic Society?s contributions to our (Turkish) poliphonic music
Keywords: Müzik; Filarmoni; Konservatuvar; Orkestra; çoksesli müzik; İstanbul; Music; Philarmonic; conservatoire; orchestra; poliphonic music; Istanbul